(untitled) (Advances in Applied Mathematics and Mechanics, 2019)
This paper is a generalization of some recent results concerned with the lower bound property of eigenvalues produced by both the enriched rotated Q_1 and Crouzeix-Raviart elements of the Stokes eigenvalue problem. The main ingredient is a novel and sharp L^2 error estimate of discrete eigenfunctions, and a new error analysis of nonconforming finite element methods.